The attachment style influence on interpersonal relationships creation features at girls - M. Takmakova, (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article considers attachment style influence on the interpersonal relationships satisfaction level and the loneliness experience among girls. Research sample comprised girls aged early adulthood and adolescence, which was established four possible attachment style: "Autonomy," "Overdependence", "Pseudoautonomy" and "Disorientation". The results suggest that disturbance attachment styles are associated with the inter- personal relationships idealization, fear of partner losing an increased tendency to diffuse loneliness experience. Intensity of social attitudes to dependence and independence affiliation in relationship form a common interpersonal relationships violations factor, which generates a strong feeling of leaving, loneliness and isolation in the relationship.
Keywords: attachment style; interpersonal relationships